Resolva a equação do 2° grau incompleta
![{x}^{2} - 6x = 0 {x}^{2} - 6x = 0](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++-++6x+%3D+0)
Soluções para a tarefa
Respondido por
3
x² - 6x = 0
a= 1, b= -6, c= 0
∆= b² -4.a.c
∆= (-6)² -4.1.0
∆= 36
x= -b±√∆ /2.a
x'= 6+6/2.1
x'= 12/2
x'= 6
x"= 6-6/2
x"= 0/2
x"= 0
S= {6, 0}
Bons estudos! :)
a= 1, b= -6, c= 0
∆= b² -4.a.c
∆= (-6)² -4.1.0
∆= 36
x= -b±√∆ /2.a
x'= 6+6/2.1
x'= 12/2
x'= 6
x"= 6-6/2
x"= 0/2
x"= 0
S= {6, 0}
Bons estudos! :)
Respondido por
0
x² - 6x= 0
x • (x - 6)= 0
x= 0
x - 6= 0
x= 6
S= ( 0 , 6)
Perguntas interessantes
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Psicologia,
11 meses atrás
Geografia,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás